Treatment options for locally advanced breast cancer--experience in an Asian tertiary hospital - Chong, H.Y.; Taib, N.A.; Rampal, S.; Saad, M.; Bustam, A.Z.; Yip, C.H. (West Asia Organization for Cancer Prevention, 2010)
Patients who had primary surgery had better survival than those who underwent neoadjuvant chemotherapy, which may be due to bias in the selection of patients for neoadjuvant chemotherapy. Out of a total of 155 patients, 25.1% defaulted part of the treatment, or did not receive optimal treatment, emphasizing the importance of psychosocial support and counselling for this group of patients.